Steroid-responsive dual neuronal antibody-positive paraneoplastic encephalitis (Indian Journal of Case Reports, 2024)
Here, we report the case of an elderly African male with multifocal neuraxial involvement in the form of progressive parkinsonism and ataxia over a year. On evaluation, dual neuronal antibody positivity was detected. A diagnosis of paraneoplastic encephalitis was made without any detection of primary neoplasm. He was successfully managed with pulse steroid therapy followed by oral steroid and steroid-sparing oral immunosuppressive drug without any need for intravenous immunoglobulin or plasma exchange.